Selection methods used by executive search consultancies in four European countries: A survey and critique - CLARK, Timothy Adrian Robert (Institutional Knowledge at Singapore Management University, 1993)
This article identifies two deficiencies in the existing literature on selection methods used for the recruitment of managers: 1. The central focus has been the relationship between the employing organization and the applicant/candidate. It has been assumed that all managerial employees are recruited directly by the employing organization. As a consequence, only the selection methods used by the employer have been examined. 2. Few researchers have considered managerial selection from a cross‐national perspective, particularly in relation to the use of external recruitment consultancies. These two issues are the central concern of this article. The use of external executive recruitment consultancies is examined in four European countries: France, Germany, Italy and the UK. Results are presented from two studies on the use of selection methods by such consultancies. A significant difference between France and the UK, and these two countries and the other two, in their use of references and graphology is reported. The evidence shows that, in general, German, Italian and UK search consultancies use low validity techniques, primarily unstructured interviews and references, while France makes use of these two methods in addition to graphology. It is suggested they use low validity selection methods because validity is not the primary ‘evaluative standard’by which the usefulness of selection methods are assessed. Five alternative ‘evaluative standards’are suggested: client expectations, role of consultants, consultant qualifications, impact on candidates and importance of characteristics being assessed. The utilization of different selection methods by search consultancies located in the four countries is negligible. This may be due to three factors: organizational (the form of international search network adopted), individual (the multi‐cultural background experiences of consultants) and external (the nature of clients served).